(3bUjOI aj QKGA UGOb GdaMGes - (3MSjf Hf EHQGgje LGhT GdMdjs
(3ChdgG (B:s
(3dfGXegG QGKjkG heDQNkG YGe haGI GdSjO UGOb GdaMGe OY PcQ ScGf GdZQjH hHGQb hGNdY MHGHGJ GdYejO GdYGTb s
(3BNQgG (B:s
(3eG cGf YeQc SjOj aj fGXQj MJi CfbVi EdG cheVI HGQb s
(3Vef eLehY , JQJjHgG (B: (3BNQgGs
(3GdeQKj UGOb Hf eMeO Hf GdMSf Hf gGTe GdMSjfj GdeYQha HGdaMGe GdeJhai (B1204 (3g```s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B116 s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI HGdfLa (B(287) s
Keywords: (3GdCOHs